2002
DOI: 10.1302/0301-620x.84b3.12204
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Kotz type of tumour endoprosthesis for the lower limb

Abstract: In 251 patients over a period of 15 years an uncemented Kotz modular femoral and tibial reconstruction mega prosthesis was implanted after resection of a malignant tumour of the lower limb. Twenty-one patients (8.4%) underwent revision for aseptic loosening, again using an uncemented prosthesis, and five of these required a further revision procedure. The median follow-up time from the first revision was 60 months (11 to 168) and after a second revision, 33 months (2 to 50). The probability of a patient avoidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 32 publications
(19 reference statements)
1
33
0
8
Order By: Relevance
“…Malo et al [44] reported modular implants were associated with an improved MSTS functional score among 56 patients. Numerous authors [8, 43, 48, 70] have similarly reported modular endoprostheses survive longer than historical custom-designed implants. In our series, the mean time to revision of the four failures among modular implants was 12.5 months (range, 1.6–21.4 months), indicating these failures were possibly the result of technical error rather than implant design (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malo et al [44] reported modular implants were associated with an improved MSTS functional score among 56 patients. Numerous authors [8, 43, 48, 70] have similarly reported modular endoprostheses survive longer than historical custom-designed implants. In our series, the mean time to revision of the four failures among modular implants was 12.5 months (range, 1.6–21.4 months), indicating these failures were possibly the result of technical error rather than implant design (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it difficult for surgeons to accurately predict how long the implants will last for a given patient population and life expectancy. Additionally, there are limited data available with which to compare implant survival of contemporary modular implant designs with older custom-designed implants no longer in use [8, 44, 48, 70]. Critics of a cemented endoprosthetic reconstruction technique cite rates of aseptic loosening from 8.4% to greater than 30% [2, 30, 38, 63] as the main rationale for abandoning its use in favor of newer designs.…”
Section: Introductionmentioning
confidence: 99%
“…Freedman and Eckardt reported a similarly small series of nine patients, with an average group follow-up of 17 months, who also received a Howmedica modular endoprosthesis, one of which was revised for aseptic loosening (11%), and a second for infection (combined =22%) [12]. Slightly longer rates of interval follow-up were reported by Mitermayer et al in a study of 251 uncemented Kotz modular implants over 15 years; an 8.4% revision rate due to aseptic loosening, after a mean of 36 months, was described [26]. Unwin et al reported in 1996 the long-term follow-up of patients receiving 1,001 custom made Stanmore implants in the lower extremities, 493 of which were in the distal femur.…”
Section: Discussionmentioning
confidence: 99%
“…Refined surgical techniques have led to a low complication rate with long follow-up periods [14,31,[35][36][37]. Comparable results with similar cemented [10,12,17,25,33,34] and non-cemented [3,26] implants have been reported from many international centers, establishing conventional stemmed technology as the current standard of care for such indications.…”
Section: Introductionmentioning
confidence: 99%
“…Endoprosthetic reconstruction is the most popular method and has advantages such as immediate stability, short operative time, and relative suitability for patients who require adjuvant therapy. However, long-term mechanical complications and difficulty in soft tissue attachment are still problematic [911]. On the other hand, biological osteoarticular allografts have shown limited success [4, 1214].…”
Section: Introductionmentioning
confidence: 99%